1991
DOI: 10.1051/rnd:19910602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an acute exposure of rat testes to gamma rays on germ cells and on Sertoli and Leydig cell functions

Abstract: Summary ― Germ cells and Sertoli and Leydig cell functions were studied from 7 to 180 days after an acute exposure of 2-month-old rat testes to 9 Gy of y rays. Body weight, testis and epididymal weights were recorded. Sertoli cell parameters (androgen-binding protein, ABP, in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
(50 reference statements)
4
16
1
Order By: Relevance
“…Consequently, we suppose that an increase of germ cell death could modify the production of proteins or other factors by Sertoli cells. Indeed, some authors have suggested that a diminution of ABP production by Sertoli cells in c-irradiated rats could have been due to germ cell death caused by radiation (Pinon-Lataillade et al 1991;Guitton et al 2000). Based on these authors' data, we suppose that the transferrin labeling diminution observed in Sertoli cells of etoposide-treated groups occurred due to the loss of germ cells, since etoposide caused an increase of apoptotic germ cell death in rats treated during prepubertal phase, as previously demonstrated by us (Stumpp et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we suppose that an increase of germ cell death could modify the production of proteins or other factors by Sertoli cells. Indeed, some authors have suggested that a diminution of ABP production by Sertoli cells in c-irradiated rats could have been due to germ cell death caused by radiation (Pinon-Lataillade et al 1991;Guitton et al 2000). Based on these authors' data, we suppose that the transferrin labeling diminution observed in Sertoli cells of etoposide-treated groups occurred due to the loss of germ cells, since etoposide caused an increase of apoptotic germ cell death in rats treated during prepubertal phase, as previously demonstrated by us (Stumpp et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In Wistar [22] or Sprague-Dawley rats [29] there was a 50-70% increase in serum FSH following 5 Gy to 20 Gy irradiation of testes; serum LH was increased 1.4-to 4-fold. In these studies, no recovery of spermatogenesis was seen after 5-20 Gy.…”
Section: Serum Hormone Levels After Irradiationmentioning
confidence: 92%
“…In contrast to nongenotoxic agents, the only genotoxic agents that have any hormonal or mechanistic data are cadmium (Bomhard et al, 1987;Laskey and Phelps, 1991;Waalkes and Rehm, 1992), dibromochloropropane (DBCP) (Cortes-Gallegos et al, 1980;), and radiation (Lindsay et al, 1969;Pinon-Lataillade et al, 1991). These compounds are discussed below.…”
Section: B Genotoxic Compoundsmentioning
confidence: 99%
“…The incidence of LCTs was 1/45 (2/2%), 6/62 (9.7%), and 40/74 (54%) in the control, 150R, and 500R groups, respectively. The ability of radiation to induce LCTs may be related to increased LH levels (Pinon-Lataillade et al, 1991), possibly secondary to tubule damage. Interestingly, other radiation studies with rats did not demonstrate an association with radiation and LCT formation (Hulse, 1977;Anisimov and Osipova, 1993).…”
Section: Radiationmentioning
confidence: 99%